'Do U txt?' – Using ' txting ' to learn maternal languages: a Portuguese case study. (1st April 2011) - Moreira, Sandra Côrtes; Gomez, Ignácio Aguaded
Analysing the influence of new technologies/media (e.g., mobile phones, chats, instant messaging services) on the use and learning of maternal languages basic rules is the goal of this investigation, involving teachers and students (10th, 11th and 12th grade pupils, aged between 16 and 21) at the Escola Secundária de Silves – ESS (Algarve/Portugal), and extended to include at the Irish School of St. Tiernan's Community (Dublin/Ireland). The use of txting, commonly pointed out as being responsible for the destruction of correct knowledge/mastery of maternal language rules in younger people is, however, in our opinion, one more factor proving the constant adaptability/transformation of languages, revealing the user's high creativity, ability to synthesise and to introduce – in txting itself – different language skill levels. Exercises using txting were developed/applied at the ESS, proving to be motivational (both for students and teachers) and efficient in transmitting Portuguese language rules.